IMPACT OF LEVERAGE, FIRM SIZE, AND PROFITABILITY ON EARNINGS MANAGEMENT - Ramadhani, Syahfani Novia; Fauzan, Fauzan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Earnings management is an action taken by management to manage earnings in financial statements. This study analyzes the effect of leverage, firm size, and profitability on earnings management in energy sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The results provide empirical evidence that leverage and firm size influence earnings management. Meanwhile, profitability has no effect on earnings management. These findings provide insights for companies, investors, and stakeholders in understanding the factors that influence earnings management practices.